1998
DOI: 10.1007/bf03011986
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and electroencephalograph responses to intubation during induction with propofol or propofol/fentanyl

Abstract: with propofol or propofol/fentanylPurpose: To observe the changes in EEG bispectral index (BIS), 95% spectral edge frequency (95% SEF) and median frequency (MF)with haemodynamic changes to intubation during induction with propofol or propofol and 2 ~ug.l,,g -I fentanyl/v. Methods: Twenty four ASA I-II patients were randomized to receive either propofol infusion preceded by normal saline (group P, n= 12) or propofol preceded by 2/./g.kg -I fentanyl (group PF, n= 12). Intubation was performed five minutes after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 8 publications
6
40
0
1
Order By: Relevance
“…[11][12][13] However, to our knowledge, there have been no reports on the effects of abrupt increases in isoflurane and sevoflurane concentrations on BIS. Since BIS has been shown to be increased by stimuli to the airways, such as endotracheal 14 and mechanical stimulation of the nasal mucosa, 15 it is possible that the administration of a high concentration of isoflurane will increase BIS. The objective of the present study was to elucidate the changes in hemodynamics and BIS after rapid increases in isoflurane and sevoflurane concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] However, to our knowledge, there have been no reports on the effects of abrupt increases in isoflurane and sevoflurane concentrations on BIS. Since BIS has been shown to be increased by stimuli to the airways, such as endotracheal 14 and mechanical stimulation of the nasal mucosa, 15 it is possible that the administration of a high concentration of isoflurane will increase BIS. The objective of the present study was to elucidate the changes in hemodynamics and BIS after rapid increases in isoflurane and sevoflurane concentrations.…”
mentioning
confidence: 99%
“…7 It has been suggested that a reflex response to a noxious stimulus to the airway is mediated at the subcortical level 14,15 and thus may be unrelated to the state of consciousness. 11 Therefore, the BIS value, which reflects cerebral cortical activity, is not influenced by noxious stimuli.…”
mentioning
confidence: 99%
“…due to tracheal intubation is mediated at the subcortical level, 4 peripheral stimuli reach the brain through the ascending reticular activating systems of the brain stem and may affect the state of consciousness. 9 Mi et al 4 reported that BIS was significantly increased by laryngoscopy and intubation during infusion of propofol with or without fentanyl pretreatment. Guignard et al 5 demonstrated that laryngoscopy and intubation were associated with an increase in BIS during target-controlled infusion of propofol.…”
Section: Méthode : Trois Minutes Après L'induction De L'anesthésie Avmentioning
confidence: 99%
“…[1][2][3] Previous studies have shown that tracheal intubation is associated with increases in BIS as well as heart rate (HR) and blood pressure. [4][5][6] Therefore, intubation is likely to affect both the hypnotic and antinociceptive components of anesthesia. Although the enhanced hemodynamic response to intubation in patients with hypertension is well documented, 7,8 the degree of the arousal response has not been studied.…”
mentioning
confidence: 99%
“…Randel et al 24 have reported that patients ventilated with isoflurane in nitrous oxide and oxygen have presented sympathetic activation represented by heart rate increase without changes in pressure response to intubation, and premedication with opioids may prevent plasma epinephrine, but not norepinephrine, concentration increase after laryngoscopy and intubation. Other authors have evaluated the influence of intravenous 2 µg.kg -1 fentanyl associated to propofol in attenuating hemodynamic and cortical responses (through BIS) to intubation and have concluded that this technique has been effective in blocking hemodynamic responses without attenuating brain cortical activity response 25 . Billar et al 26 have shown that 2 µg.kg -1 fentanyl associated to propofol have decreased blood pressure and heart rate in response to intubation.…”
Section: S = K Log (W)mentioning
confidence: 99%